A proposed environmental management model of Chemistry laboratory: From procedure awareness and laboratory practices to extent of conformance to environmental management system - Tamio, Joysol B. (Animo Repository, 2022)
This research sought to find the level of procedure awareness in terms of usage of chemicals and safety in the chemistry laboratory, also the extent of laboratory practice with regards to handling and storage of reagents and disposal of wastes from the experiments and from the storage area. In addition, this study intended to determine the extent of conformance to Environmental Management System (EMS) in association with the procedure awareness and laboratory practices. This utilized the survey method that involved 335 students, and 14 chemistry faculty members and laboratory technicians from selected colleges and universities with science and technology, engineering, and mathematics (STEM) strand in Senior Highschool and pure science related disciplines in Tertiary Level. An interview was also facilitated to facility officers in addition to 12 students, and 7 chemistry teachers and laboratory technicians, who were randomly selected from the surveyed sample, for confirmation purposes. It was determined that there was a significant difference with mean values of the students’ group and the chemistry teachers/laboratory technicians’ group with regards to procedure awareness in usage of chemicals. Moreover, results turned out that the usage of chemicals has a negligible correlation with the extent of conformance to EMS. Acquiring this, the researcher did further test for possible significant relationships involving the conformance to EMS and usage of chemicals. The outcome Environmental Management Model of Chemistry Laboratory named as “TAMSS Environment – Chemistry Laboratory”, was able to show that there were mediating variables, which may be utilized to achieve a significant relationship between EMS and usage of chemicals.